From welfare state to participation society? Austerity measures and local sport policy in the Netherlands. Issue 1 (2nd January 2018) - Hoekman, Remco; van der Roest, Jan-Willem; van der Poel, Hugo
ABSTRACT: This study investigates whether the shift from welfare state to participation society in the context of austerity in the Netherlands has had consequences for local sport policy. The central research questions are (1) do municipal sport budgets show evidence of a move away from classical welfare state values towards a participation society? and (2) do changes in local sport policy suggest a move away from classical welfare state values towards a participation society? First, we analysed spending on sport across all Dutch municipalities. Second, we quantitatively and qualitatively analysed 104 municipal coalition agreements for the 2014–2018 governing period. The approach used was interpretive, focusing on dominant or hegemonic discourses or storylines within local sport policy. It shows that Local sport policy in the Netherlands still hinges strongly on welfare state values and has not yet been hit by serious austerity measures. We found no evidence of a neoliberal slant or an emphasis on free-market and private entrepreneurship. Rather, the accent is on an expanded role for voluntary sport clubs (VSCs) in operating sport facilities and as policy implementer. We conclude that the shift in narrative from classical welfare state to participation society has, as yet, had limited effect on local sport policy.